Cloning and expression of the coding regions of the heat shock proteins HSP10 and HSP16 from Piscirickettsia salmonis - WILHELM,VIVIAN (Sociedad de Biología de Chile, 2003)
The genes encoding the heat shock proteins HSP10 and HSP16 of the salmon pathogen Piscirickettsia salmonis have been isolated and sequenced. The HSP10 coding sequence is located in an open reading frame of 291 base pairs encoding 96 aminoacids. The HSP16 coding region was isolated as a 471 base pair fragment encoding a protein of 156 aminoacids. The deduced aminoacid sequences of both proteins show a significant homology to the respective protein from other prokaryotic organisms. Both proteins were expressed in E. coli as fusion proteins with thioredoxin and purified by chromatography on Ni-column. A rabbit serum against P. salmonis total proteins reacts with the recombinant HSP10 and HSP16 proteins. Similar reactivity was determined by ELISA using serum from salmon infected with P. salmonis. The possibility of formulating a vaccine containing these two proteins is discussed